The engaged caregiver how to build a performance-driven workforce to reduce burnout & transform care - Cabral, Joseph; Lee, Thomas H.; Wright, Martin (McGraw-Hill, 2020)
"From the top experts on healthcare workforce engagement comes the vital road map to reduce the alarmingly high-and fast-growing-rate of staff burnout and to transform care. More than half of U.S. physicians and 40 percent of nurses experience one or more symptoms of burnout. This crisis poses a serious threat to our health systems, impacting not only the well-being of the caregiving workforce but also that of patients. Written by a team of thought leaders with deep expertise in healthcare workforce engagement and cultural development, The Engaged Caregiver offers a detailed guide for leaders, managers, and front-line providers to identify, diagnose, measure, and develop strategies to address and overcome caregiver burnout. It's an actionable plan for developing and building a resilient culture that empowers caregivers and gives them the support they need to fulfill the patient promise with every care experience, every day"--